Demokrat Parti döneminde (1950-1960) uygulanan iktisat politikalarının nüfus hareketlerine etkisi - Altun, Fikret (My University, 2025)
Bu çalışmada, 1950-1960 yılları arasında Türkiye'de Demokrat Parti tarafından yürütülen iktisat politikalarının nüfus dinamiklerine olan etkileri ele alınmıştır. Bu dönem, Türkiye'nin politik ve ekonomik tarihinde kritik bir evre olarak kabul edilmiş ve Demokrat Parti'nin iktidara gelmesiyle ekonomi politikalarında önemli değişiklikler yaşanmıştır. Çalışma, Demokrat Parti'nin serbest piyasa odaklı politikalarını, özellikle tarıma yönelik destekleri ve özel sektörü teşvik eden yaklaşımlarını incelemektedir. Bu politikaların, kırsal kesimde yaşayan insanların ekonomik durumunu ve yaşam standartlarını iyileştirdiği, aynı zamanda sanayileşme ve şehirleşme süreçlerini hızlandırdığı görülmüştür. Ancak, bu politikaların etkileri her alanda eşit olmamıştır. Kırsal alanlardaki gelişmelerin aksine, şehirlerde nüfus artışı ve işsizlik gibi sorunlar da beraberinde gelmiştir. Bu tez, Demokrat Parti'nin uyguladığı ekonomi politikalarının nüfus üzerindeki çeşitli etkilerini ayrıntılı bir şekilde incelerken, bu dönemin ekonomik ve sosyal yapısına derinlemesine bir bakış sunmayı hedeflemektedir.

This research examines the effects of economic policies implemented by the Democrat Party in Turkey during the years 1950-1960 on population dynamics. This period is considered a critical phase in Turkey's political and economic history, marked by significant changes in economic policies following the Democrat Party's rise to power. The research focuses on the Democrat Party's free market-oriented policies, particularly its support for agriculture and incentives for the private sector. These policies have been observed to improve the economic situation and living standards of people living in rural areas, as well as accelerating industrialization and urbanization processes. However, the impacts of these policies have not been uniform across all areas. Contrary to the developments in rural areas, urban centers have experienced issues such as population growth and unemployment. This thesis aims to provide an in-depth look at the economic and social structure of this period, thoroughly analyzing the varied effects of the Democrat Party's economic policies on the population.
The impact of economic policies during the Democratic Party period (1950-1960) on population movements
Keywords: 1950-1960; Demokrat Parti; Demokrat Parti (Turkey); Demokrat Parti (Türkiye); Economic Policies; Economic policy; Ekonomik politikası; Göç Democrat Party; İktisat politikaları; Migration; Nüfus; Nüfus hareketleri; Nüfus politikası; Population; Population Movements; Population policy; Turkey; Türkiye